pemanfaatan ekstrak kulit buah manggis (Garcinia mangostana L.) sebagai pewarna alami jaringan daun dan batang krokot (Portulaca oleracea L.) - Yani, Gita Fitri; Abbas, Muachiroh; Samiyarsih, Siti (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
The dye functions to clarify the plant tissue that will be observed with a microscope, the dye that is commonly used is synthetic dyes that are carcinogenic, the price is expensive and can pollute the environment. Natural dyes are an alternative to synthetic dyes because they are safe, inexpensive and environmentally friendly. natural dye sources obtained from plant parts such as fruit peels. Efforts to use mangosteen rind waste as an herbal remedy can also be used as a natural dye because it has a high enough anthocyanin content. Anthocyanins in mangosteen peel can be obtained through extraction. Maceration is an easy extraction method where the results are only affected by the type of solvent and the extraction time. Purslane (Portulaca oleracea L.) is used as research material because currently purslane has been widely used because of its nutritional content including high metabolic and antioxidant regualting substances. This study aims to determine the ability of mangosteen rind extract in coloring the leaf and stem tissue of purslane, and to determine the type of solvent and optimal immersion time to produce mangosteen rind extract so that it can color the leaf tissue and stems purslane well. The study was conducted experimentally using a Completely Randomized Design (CRD) with 2 factors: factor 1 was the type of solvent using ethanol 96% and citric acid 14%, the second factor was immersion time, namely 26, 27 and 28 hours. The data obtained were analyzed descriptively qualitatively including the contrast and clarity of the preserved tissue preparation of leaf and stem purslane. The results showed mangosteen rind extract has the ability to dye leaf tissue and stems. The type of 14% citric acid solvent with 28 hours soaking time was optimal in producing mangosteen rind extract so that it was able to dye the leaf and stem tissue of purslane.